2014
DOI: 10.1001/jamaoto.2014.1730
|View full text |Cite
|
Sign up to set email alerts
|

Normal-like Motor Speech Parameters Measured in Children With Long-term Cochlear Implant Experience Using a Novel Objective Analytic Technique

Abstract: Despite significant improvements in speech after cochlear implantation, abnormalities remain, particularly in frequency variability. Such deviations can present as a decreased expression of emotion in speech and likely reflects decreased auditory frequency resolution provided by the CI. These deficits have been the focus of ongoing work to advance CI technologies and speech-processing strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 23 publications
1
4
1
Order By: Relevance
“…Moreover, these populations exhibited more significant fluctuation in fundamental frequency (F0) and amplitude (Am) during sustained constant vowel production. These abnormal features gradually improve after cochlear implantation (9–11). These results confirm that auditory input via CI contributes to the development of voice skills controlling pitch and loudness.…”
supporting
confidence: 68%
See 2 more Smart Citations
“…Moreover, these populations exhibited more significant fluctuation in fundamental frequency (F0) and amplitude (Am) during sustained constant vowel production. These abnormal features gradually improve after cochlear implantation (9–11). These results confirm that auditory input via CI contributes to the development of voice skills controlling pitch and loudness.…”
supporting
confidence: 68%
“…These results indicate that congenitally deaf people, regardless of their age at cochlear implantation, had a lower ability to maintain a constant voice pitch and loudness than normal controls, even more than 10 years after implantation. The previous study using the conventional sustained vowel production task reported that in congenitally deaf CI users, vF0 and vAm gradually improved but remained significantly larger than controls 7 years after cochlear implantation (11). Thus, our results imply that neither a longer duration of CI use nor earlier implantation age is sufficient for deaf children to develop normal-like speech motor control to maintain voice pitch and loudness.…”
Section: Discussioncontrasting
confidence: 45%
See 1 more Smart Citation
“…34,35 Common short-term measurements of vocal stability-jitter and shimmer-which measure variation of pitch and loudness, respectively, within single utterances, have similarly been found to increase in hearing impaired individuals, 37 which is consistent with decreased vocal stability. Following CI, both jitter and shimmer decrease in some prelingually deaf children, 34,36,38 approaching normal ranges. Other studies have suggested that both jitter and shimmer in deaf children do not significantly differ from NH either before or after implantation.…”
Section: Cochlear Implants and Voicementioning
confidence: 93%
“…It is defined as the ability to perform fast repetitions of relatively simple patterns composed of oppositional contractions (9) , which may suggest information about individuals' neuromotor integration and maturation (9) . This acoustic evaluation has been used in several cases and populations, such as in children with speech sound disorders (10) , cochlear implants (11) , and fluency disorder (12) , in neurological patients (13)(14)(15)(16) , healthy elderly individuals (17) , youngsters and children (18,19) , as well as in patients with behavioral dysphonia (20,21) . Considering the DDK evaluations in clinical speech-language practice, laryngeal DDK aims to investigate neuromotor control of vocal folds (22) , being used mainly for the assessment of voice disorders (13,15,17,18,20,22) .…”
Section: Introductionmentioning
confidence: 99%